Faktor-Faktor yang Mempengaruhi Minat Mahasiswa untuk Mengikuti Ujian Chartered Accountant dengan Pendekatan TPB - Fikri Rizki Utama; Yudhistira Ardana (Penerbit Goodwood, 2022)
Purpose: This study was to obtain empirical evidence about the effect of subjective norms, control, and outcome expectations on the interest of accounting students to take the Chartered Accountant (CA) exam. Method: The population of this research is the Islamic accounting students of IAIN Metro. The sampling method was purposive sampling with the criteria of 2017 and 2018 accounting students. Data from the questionnaire were processed using the Smart-PLS version 3.3.9 program. Results: This study finds that behavioral control variables and expectations will have a significant effect on students' interest in taking the CA exam. Limitation: This study finds that future research is the need to increase the number of respondents and others such as the attitude of the respondents to the students' interest in taking the CA exam. Contribution: The findings in this study have several contributions, particularly for accounting students who will take the CA exam. In addition, this research will be useful for academics, especially further research and for the advancement of accountants in Indonesia.